Zn2+–DNA interactions in aqueous systems: A Raman spectroscopic study. Issue 3 (2009) - Muntean Muntean, Cristina M. Cristina M.; Nalpantidis Nalpantidis, Konstantinos Konstantinos; Feldmann Feldmann, Ingo Ingo; Deckert Deckert, Volker Volker
Abstract : The influence of Zn 2+ ions on the structure of natural calf thymus DNA was studied by Raman spectroscopy. Measurements were done at room temperature and pH 6.2±0.1, in the presence of 10 mM Na +, and of Zn 2+ in a concentration range varying between 0 and 250 mM, respectively. No condensation of DNA was observed. As judging from the marker bands near 681 cm −1 (dG), 729 cm −1 (dA), 752 cm −1 (dT), and 787 cm −1 (dC, dT) altered nucleoside conformations in these residues are supposed to occur, in different intervals of Zn 2+ ions concentration. Changes in the conformational marker centered around 835 cm −1, upon Zn 2+ binding to DNA, were detected. Binding of zinc(II) ions to the charged phosphate groups of DNA, stabilizing the double helical structure, is indicated in the spectra. We have found that binding of metal ions at N3 of cytosine takes place at zinc(II) concentrations between 150–250 mM and interaction of Zn 2+ ions with adenine is observed in a concentration range from 10 to 250 mM. Binding of zinc(II) ions to N7 of guanine and, possibly, in a lesser extent to adenine was also observed as indicated by the Raman marker bands near 1490 and 1581 cm −1 . There is no intensity change of the band at 1668 cm −1, suggesting no change in their base pairing and no change induced in the structure of water by Zn 2+ cations. No evidence for DNA melting was identified.